1487 The Pied-Piper, How Gastroenteritis Led Us Astray. Fibromuscular Dysplasia: A Surgical Perspective of a Rare Vascular Disorder. (12th October 2021) - Davis, H; Mishra, S; Adams, L; Culmer, C; Shrestha, A
Abstract: : A 73-year-old female was admitted for abdominal pain after eating an out-of-date pie. She was treated for gastroenteritis for 48hours, after which she became unexpectedly haemodynamically unstable. Computerised Tomography (CT) suggested mesocolic arterial bleed with a large mesenteric haematoma. CT angiography confirmed false aneurysms of the middle colic artery and multiple beading of coeliac branches, small mesenteric vessels and the inferior mesenteric artery. Opinion was sought from multiple specialties, pseudoaneurysm embolisation was undertaken and steroids commenced for presumed vasculitis. Vasculitis screen was negative, and PET CT scan showed no metabolically active vasculitis. It was felt a diagnosis of fibromuscular dysplasia (FMD) was likely. Steroids have been weaned and the patient is under active observation. Background: FMD is a rare idiopathic condition of abnormal cellular growth in medium/large arterial vessel walls. It has a frequency of approximately 0.02%, predominantly affecting middle-aged Caucasian women. It manifests mostly in renal and cerebrovascular arteries and can present as hypertension or stroke. Complications include aneurysms, stenosis and dissections. Characteristic angiographical finding is a "beads on a string" appearance. There is no current cure, but surgical or interventional involvement by angioplasty and stenting may play a role treatment. Conclusions: This case elegantly highlights the ambiguity in diagnosis of abdominal pain in a general surgical setting; with a wide variety of differentials spanning multiple specialties, it emphasises the importance to consider rare presentations of equally rare pathologies. It is a celebration of the merits of a multi-disciplinary approach to solve complex clinical questions.